Estimation of Surface Water Potential in Manokwari Regency Using Remote Sensing Data - Arif Faisol; Bertha Ollin Paga; Mashudi Mashudi; Budiyono Budiyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Water availability is major issue in Manokwari Regency, and information on its surface water potential has not yet been available. This study aimed to estimate the surface water potential in Manokwari using remote sensing data, namely EROS Visible Infrared Imaging Radiometer Suite (eVIIRS) images acquired in August–September 2024 and Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) data from 1981–2023. The analysis consisted of three main stages: data inventory, runoff coefficient estimation, and surface water potential calculation using the Melchior method. The results showed that the surface water potential in Manokwari was 2,018.70 m³/s at 99% probability and 4,148.60 m³/s at 80% probability. These values exceed the 2024 water demand, indicating that Manokwari is in a surplus water condition. The findings demonstrate the usefulness of satellite-based rainfall and land cover data for hydrological assessments in areas with limited ground observation stations.